The cDNA Cloning and Molecular Characterization of a Snake Venom Platelet Glycoprotein Ib-binding Protein, Mamushigin, from Agkistrodon halys blomhoffii Venom - Sakurai, Yoshihiko; Fujimura, Yoshihiro; Kokubo, Tetsuro; Imamura, Kouji; Kawasaki, Tomihisa; Handa, Makoto; Suzuki, Masami; Matsui, Taei; Titani, Koiti; Yoshioka, Akira (Thrombosis and Haemostasis, 1998)
The entire cDNA sequences of a novel snake venom platelet glyco-protein (GP) Ib-binding protein (BP) composed of an α/β heterodimeric structure, termed mamushigin, from Agkistrodon halys blomhoffii were determined, that include the leader peptides (21/23 amino acid residues) and mature subunits (136/123 amino acid residues). The mature subunits of mamushigin are 37.5% identical, and showed a high degree of similarity (37.7-67.5% identity) with the respective subunits of group VII C-type lectins (19). The sequences of the leader peptides of the mamusigin subunits showed the highest similarity (α-73.9/ β-82.6%) with those of factor IX/X-BP from Trimeresurus flavoviridis, and the cleavage site residue in both proteins was the same Ala–1.The GPIb-binding specificity of mamushigin is strongly supported by several lines of evidence, but mamushigin can directly aggregate normal platelets, similar to alboaggregin-B (AL-B) (1). This differs from other GPIb-BP’s. In mamushigin-treated platelets, serotonin was not released, and flow cytometric analysis using a monoclonal antibody PAC-1 totally excluded platelet GPIIb/IIIa activation. Mamushigin enhanced platelet aggregation at low-shear stress, and this effect totally disappeared in the presence of GPIb-receptor blockers specific for von Willebrand factor binding, but not by GPIIb/IIIa-receptor blockers. At high-shear stress, mamushigin blocked platelet aggregation in a dose-dependent manner, as seen with other GPIb-BP’s. This paper, therefore, describes the cDNA cloning and molecular characterization of mamushigin which has a different effect on platelet aggregation under different shear stress.